RASA3, a Key Player in Dopamine D2S Receptor-mediated MAPK Signaling - Ma, Xun (Université d'Ottawa / University of Ottawa, 2011)
The short form of dopamine D2 receptor (D2S) functions as a presynaptic autoreceptor on dopamine neurons and has an inhibitory effect on dopaminergic tone. D2-MAPKs pathway is involved in many physiological events like production of prolactin and tyrosine hydroxylase (TH) expression. However, the effect of D2S receptor signalling on MAPKs is cell type specific, and is not fully understood.A recent study in our lab has identified a Gαi-interacting ras-MAPK inhibitor RASA3. Here, we showed that RASA3 is the key effector in D2-induced inhibition of MAPK by knockdown of endogenous RASA3 in the GH4 cell using RASA3 siRNA. We have also transfected a dominant negative RASA3 to compete with the endogenous RASA3 for the binding site on Ras. Both RASA3-siRNA and dominant negative RASA3 blocked D2S-induced inhibition of MAPK activation, clearly implicating that RASA3 is a key effector in Gαi3-dependent D2S mediated MAPKs inhibition To determine whether RASA3’s inhibitory effect could be reconstituted in fibroblast cells, the effect of RASA3 on D2-mediated ERK1/2 activation in COS7 cells was tested. Our results show that both active Gαi2 (or Gαi3) and active RASA3 are required for optimal inhibition of ERK1/2 activation in fibroblast COS7 cells.
Keywords: Dopamine; ERK signaling; RASA3